Design and Application of RFID Microcontroller-Based Starter System Using Sim Card (Driver's License) - Kasum Kasum; Alber Kasman (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2023)
A Driver's License (SIM) is proof of registration and identification given by the Indonesian National Police to a person who has met administrative requirements, is physically and spiritually healthy, understands traffic regulations and is skilled in driving a motor vehicle and has a driver's license as one of the safety drivers, where when a person has a driver's license, it indicates that a person is fit to carry a vehicle. The purpose of this final project is to make a driver's license or driver's license a special key for motor vehicles that have many benefits. The system, which is designed using RFID cards, will detect cards that already have a special id. The controller used is an atmega328 microcontroller. The relay is used as a switch that serves to disconnect the current from the motor battery to the starter system and output to the alarm buzzer. The way this RFID-based starter system works is that when the rfid is registered in the microcontroller program, the rfid can be used to start the machine by bringing the rfid closer to the rfid reader tag, then the reader tag will read the rfid card on the microcontroller system and be forwarded to the relay, then to the starter motor , then the engine starts, then when the rfid is not registered, the buzzer The alarm will turn on. With RFID cards, it prevents underage or unlicensed drivers and drivers always carry their driver's license. Motorized vehicles can be kept safe, they must use an RFID card that has been registered and if it is not registered, it can be read by the system, then the buzzer alarm sounds.